BPJS Employment Strategy in Guaranteeing Occupational Health and Safety (OHS) for Non-Wage Earners (NWE) in the Fisheries Sector - Lisa Wati; Fitriani Fitriani; Rismawati Rismawati; Ernawati Ernawati; Marniati Marniati (Health Dynamics, 2024)
Background: BPJS (Badan Penyelenggara Jaminan Sosial or Social Health Insurance Administration Body) employment data for Meureubo District in 2023 shows that 85 work accident victims died or disappeared during inclement weather, and 18 out of 21 fishermen who had minor accidents required occupational health and safety insurance. However, out of over 500 fishermen in the district, only 176 are registered with BPJS Employment. This study aims to explore BPJS Employment’s strategy in ensuring occupational health and safety for non-wage workers in the fishing sector. Methods: The research employs a qualitative method with a descriptive approach, using observation and interviews for data collection. The study includes seven informants: four fishermen as main informants, and three key informants - the head of participation, a special account representative, and a case manager. Data analysis involves data reduction, data presentation, and drawing conclusions. Results: BPJS Employment's strategy includes urging agencies to protect fishermen's rights, conducting promotive and preventive outreach, creating informational materials, engaging in regional empowerment, and employing a 3-4-5 strategy (three main strategies, four focuses, and five key elements). These efforts aim to increase awareness and participation among fishermen. Conclusion: BPJS Employment Meulaboh faces several obstacles, such as limited understanding of the program among local government and communities, low public awareness about the importance of social security, and irregular income among fishermen, hindering their ability to pay contributions. Consequently, the goal of ensuring occupational health and safety in the fishing sector remains unachieved, as many fishermen are not registered with BPJS Employment.